Menanggung Dunia Terlalu Cepat: Pengalaman Psikologis Anak Sulung sebagai Penopang Keluarga Diusia 20-an - Sengkey, Marssel Michael; Sinaulan, Nova Lisye; Runtu, Savitska Svetlania; Runtu, Chevas Valentino Yohanes; Matahari, Bellen Nhiralti (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to understand the psychological experiences of firstborns in their 20s who assume the role of family breadwinners. In the context of a collectivistic culture such as Indonesia, firstborns are often required to take on great responsibilities both emotionally and financially, which can give rise to their own psychological stress, especially when experienced during the transition period of early adulthood or quarter-life crisis. This study uses a qualitative approach with an interpretative phenomenological analysis (IPA) method to explore in depth the subjective meaning of the experience of a participant who meets the criteria as a firstborn aged 20–29 and plays the role of family breadwinner. The results of the study indicate that this role is generally not a conscious choice, but rather a response to a family crisis that results in the parentification process. Participants experience a double burden as breadwinners and emotional breadwinners, with psychological consequences such as anxiety, inner conflict, guilt, and delaying personal aspirations. However, aspects of psychological resilience and positive meanings were also found that were successfully constructed from this experience. These findings highlight the need for psychosocial support for firstborns who experience similar burdens, as well as the importance of recognizing the psychological impact of role dynamics in the family.